PERMEABILITY OF INTERLANGUAGE SYSTEM: A CASE STUDY OF STUDENTS LEARNING ENGLISH AS A FOREIGN LANGUAGE AT SMP MUHAMMADIYAH 5 SURAKARTA - Maryana, Lestari Kelik (Jurnal Penelitian Humaniora, 2016)
The research deals with permeability of studentsâ interlanguage system that reflects in studentsâ composition of SMP Muhammadiyah 5 Surakarta. The aims of the research are (1) to describe what the types of permeability, (2) to describe the sourceof the influence in studentsâ IL system, and (3) to describe the influence frequency of studentsâ IL system. The type of this research is qualitative research. The data of this research are erroneous sentences found in the studentsâ compositions. The method of collecting data is elicitation and document analysis. The writer uses descriptive analysis by Celce Marcia and a modified framework of Error Analysis by Shridar a technique for analyzing data. The results indicate that (1) the permeability is found atthe level of morphology and syntax, (2) the source of the influence is studentsâ mother tongue (Indonesian) and target language (English), (3) the influence frequency of the mother tongue to studentsâ interlanguage system is 48% and of the target languageto the studentsâ interlanguage system is 52%. The conclusion is that the learnersâ interlanguage is open to to influence from the outside and influence from the inside language system. It progressively approaches the target language as a result oflearnersâ attempt on constructing a new linguistic system.